Results of studying the pharmacological activity of the main sesquiterpene lactones of Laurus Nobilis Leaves - N. M. Aliyeva; V. V. Kozlova; V. N. Orobinskaya; S. A. Yemelyanov (Современная наука и инновации)
Introduction. The aim. To study the actual types of pharmacological activity of extracts and basic sesquiterpene lactones from the LaurusnobilisL. leaves of the noble laurel. Materials and methods.The work uses samples of Laurusnobilisleaves collected in the southern regions of the Russian Federation during the main phases of plant growth and development. We also used samples of Laurusnobilisleaves purchased in the retail chain from various manufacturers, which had the appropriate quality and safety certificates. The study of toxicity and antidiabetic activity was carried out using well known methods. The study of antitubercular activity was carried out by the nitrate reductase method. Results and discussion. Essential oil, sesquiterpene lactones (especially dehydrocostuslactone), in comparison with known antituberculosis drugs, show pronounced activity against clinical strains of tuberculosis. A comparison of the effectiveness of the course application of the developed collection with Laurusnobilisleaves in relation to the prototype collection (without laurel leaves) showed that the studied antidiabetic collection reduces blood glucose levels (to 7.6±0.15 mmol/L compared with 11.2 ±0.8 mmol/L when using the prototype collection and from 24.5±2.3 mmol/l in intact animals), as well as normalize the indicators of total cholesterol, β-lipoproteins and insulin. Conclusion. Essential oil and sesquiterpene lactones exhibit anti-tuberculosis activity against the studied clinical strains. The collection developed by the authors (with leaves of noble laurel) has hypoglycemic activity.